Gated Gradient-Motion-Refocused (GMR) Images with Spin-Echo Sequences - Metes, Joseph J.; Wilner, Harvey I.; Crowley, Michael; Negendank, William; Kelly, John K.; Lazo, Alfredo (American Journal of Neuroradiology, 1989)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf